ศึกษาการใช้คำวิเศษณ์บอกเวลาพ้องความหมายในภาษาเกาหลีของนักศึกษาไทย กรณีศึกษา : คำวิเศษณ์บอกเวลา “벌써-이미” “지금-이제” “어서-얼른”: A Study of Thai students’ Use of Adverbs of Time in Korean Language Case Study: Korean’s Adverb of Time “벌써-이미” “지금-이제” “어서-얼른” - สหะวิริยะ กาญจนา (Journal of Humanities and Social Sciences (HUSOKKU), 2022)
The purpose of this research was to study how Thai learners use synonymous adverbs in Korean in terms of semantic classification and correct usage according to Korean grammar. The sample group consisted of 217 third-year students majoring in Korean language. The research instrument was a competency test on the use of adverb of time, “이미-벌써” “지금-이제” “어서-얼른”. The statistics used in the data analysis were mean and percentage. The findings revealed that 1) Thai students were not able to correctly classify the meanings and terms of use according to the Korean grammar of synonymous adverbs. This is due to the fact that synonymous adverbs in Korean have their own set of semantics and grammatical words. As a result, when adverbs of time are synonymous, they convey the same meaning and can be interchanged. They are frequently perceived to have distinct meanings and are not interchangeable. The results were as follows: 1.1) the adverb “벌써” and adverb “이미” signified “past tense” these words are identical and interchangeable. But Thai students gave wrong answers with the percentage of 81.79. 1.2) the adverb “지금” and adverb “이제” implied “present simple tense” these words are similar and interchangeable. But then Thai students gave wrong answers with the percentage of 73.87. 1.3) the adverb “어서” and adverb “어른” meant “The desire to do something smoothly and continuously in the future” these words are comparable and substitutable. On the other hand, Thai students gave wrong answers with the percentage of 82.2 Thai students have a limited understanding of Korean grammatical terms related to inflectional language. The appearance of synonymous adverbs with different words and grammar, as well as their syntactic endings, can lead to confusion when selecting synonymous adverbs to match their meaning.